Music 109: Notes on Experimental Music - Lucier, Alvin; Ashley, Robert 1930-2014 (Middletown Wesleyan University Press, 2012)
Composer and peformer Alvin Lucier brings clarity to the world of experimental music as he takes the reader through more than a hundred groundbreaking musical works, including those of Robert Ashley, John Cage, Charles Ives, Morton Feldman, Philip Glass, Pauline Oliveros, Steve Reich, Christian Wolff, and La Monte Young. Lucier explains in detail how each piece is made, unlocking secrets of the composers' style and technique. The book as a whole charts the progress of American experimental music from the 1950s to the present, covering such topics as indeterminacy, electronics, and minimalism, as well as radical innovations in music for the piano, string quartet, and opera. Clear, approachable and lively, Music 109 is Lucier's indispensable guide to late 20th-century composition. No previous musical knowledge is required, and all readers are welcome.
Keywords: Musical analysis; Avant-garde